Development and Validity of the Nurse Presenteeism Questionnaire - Shan, Geyan; Wang, Shengnan; Feng, Kai; Wang, Wei; Guo, Shujie; Li, Yongxin (Frontiers in Psychology, 2021)
This study aimed to develop and test the reliability and validity of a multi-item nurses’ presenteeism behaviour questionnaire. Study 1 administered the Nurse Presenteeism Questionnaire (NPQ) to 250 Chinese nurses. Study 2, surveyed 650 nurses with the NPQ, the Sickness Presenteeism Questionnaire, the Stanford Presenteeism Scale, the General Health Questionnaire, and the Emotional Exhaustion Scale using convenience sampling. After item analysis, the subjects were randomly divided into two groups to verify the questionnaire structure. Study 1 revealed the nurses’ core symptoms when they go to work with illness, and the NPQ with 11 items was developed. Study 2’s item analysis revealed that 11 NPQ items had good discrimination (t = 22.67∼36.11, p < 0.01) and high homogeneity. Besides, the scale had good reliability (Cronbach’s = 0.93) and external criterion validity (r = 0.24∼0.84, p < 0.01). Thus, the NPQ can be used to measure presenteeism behaviour in nursing.